2015
DOI: 10.1039/c4ce02045f
|View full text |Cite
|
Sign up to set email alerts
|

Large γ-CuI semiconductor single crystal growth by a temperature reduction method from an NH4I aqueous solution

Abstract: Transparent, centimeter-sized γ-CuI single crystals with p-type conduction were successfully obtained from NH4I aqueous solutions by the temperature reduction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…While n h decreased, μ was remarkably enhanced and reached a large value of 21 cm 2 V −1 s −1 at T H = 120 °C (Figure S1, Supporting Information). Surprisingly, this μ value is higher than the reported value for a bulk single crystal of CuI (≈13 cm 2 V −1 s −1 ) . These results demonstrate that μ values as high as ≈20 cm 2 V −1 s −1 are attainable in CuI films on PET.…”
contrasting
confidence: 53%
“…While n h decreased, μ was remarkably enhanced and reached a large value of 21 cm 2 V −1 s −1 at T H = 120 °C (Figure S1, Supporting Information). Surprisingly, this μ value is higher than the reported value for a bulk single crystal of CuI (≈13 cm 2 V −1 s −1 ) . These results demonstrate that μ values as high as ≈20 cm 2 V −1 s −1 are attainable in CuI films on PET.…”
contrasting
confidence: 53%
“…Being an inorganic compound, its chemistry allows it to readily coordinate with many organic ligands and this has resulted in CuI‐based hybrid clusters with tremendous luminescent properties . It has also proven to be very promising as a transparent conducting material with excellent hole transport capabilities . Several articles reported the electrical properties of CuI but a very few have reported its thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] It has also proven to be very promising as at ransparentc onductingm aterial with excellenth ole transport capabilities. [22,28,29] Several articles reportedt he electrical properties of CuI but av ery few have reported itst hermoelectric properties.H ere,e fforts are made to improve the thermoelectric performance of this compound. Thec hange in thermoelectric behavior has been studied by thermal annealing, which leads to achangeini ts defect chemistry.Asimples ynthetic approachh as been usedt op repare the material in bulk quantity.A st he material is earth-abundant,l ow-cost, and has promising electronic properties,i tc an be useful in replacing toxic and expensive materials wherever applicable.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, g-CuI is almost insoluble in water (pK sp ¼ 11.96 at 300 K), therefore a co-solvent is required for the solution growth of g-CuI. On the basis of our previous studies, 11 we concluded that NH 4 X (X ¼ Cl, Br, I) co-solvents can effectively increase the solubility of g-CuI in water and be well suited for crystal growth via a low-temperature aqueous solution method. In this study, a home-designed temperature difference method was used for high optical quality g-CuI crystal growth with NH 4 X as the cosolvent employing a positive temperature gradient.…”
Section: Introductionmentioning
confidence: 99%